2019
DOI: 10.3390/ijerph16183371
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Secondary Eye Care Services in Western Kenya

Abstract: Background: Eye care provision is currently insufficient to meet the population’s eye health needs in Kenya. Many people remain unnecessarily visually impaired or at risk of becoming so due to treatable or preventable conditions. A lack of access and awareness of services are key barriers, in large part due to their being too few eye care providers in the health system for this unmet need. Methods: A hospital-based, retrospective analysis of patients who attended Kitale eye unit, Trans Nzoia County, Kenya from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(41 reference statements)
3
12
0
Order By: Relevance
“…In accordance to those previous studies, most cases in our sample affected the eye anterior segment, with pterygium and cataract as the most frequent abnormalities 10 , 19 21 . In terms of posterior segment, glaucoma cupping was the most observed finding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance to those previous studies, most cases in our sample affected the eye anterior segment, with pterygium and cataract as the most frequent abnormalities 10 , 19 21 . In terms of posterior segment, glaucoma cupping was the most observed finding.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study performed in the UK with over 3 million people attending eye health consultations showed that 88.1% of cases were not associated with visual impairment complaint 20 . Similar results were recently observed in India and Kenya, with conditions not associated with visual acuity decrease accounting for 59% and 52%, respectively 19 , 21 .…”
Section: Discussionsupporting
confidence: 88%
“…The resulting morbidity needs to be addressed, forming a substantial proportion of ophthalmic service work. 6 …”
Section: Section 1: the Eyes Vision Impairment And Eye Conditionsmentioning
confidence: 99%
“…Similarly, data from a secondary eye unit in Kenya found that less than half of presentations were for conditions associated with vision impairment. 6 …”
Section: Section 3: Magnitude Of Eye Diseasementioning
confidence: 99%
“…[1] Approximately, 26 million people are visually impaired and 3 million blind in sub Saharan region. [2] In Malawi, 3.3 % of the population is blind compared to 1.01 % in America. [3,4] Accordingly, visual impairment is directly related to access, Utilization and poverty.…”
Section: Introductionmentioning
confidence: 99%